Nostalgia for Crisis: Representing Revolution in North American Popular Culture - Truman, Emily (eTopia, 2009)
In contemporary North America we no longer have revolutions; instead we have nostalgia for revolution. Benjamin Arditi’s Politics on the Edges of Liberalism argues that the continued presence of marginal radical politics in Western liberal democracies is evidence of our nostalgia for revolution and that we are mourning an ideal state of the past. I argue that another more widespread site of evidence for our nostalgia for revolution is the proliferation of popular artefacts branded with revolutionary iconography. As a symbol, revolution is omnipresent in North American culture. It is on our t-shirts, magazine covers, book jackets, advertising posters,and in our language and conversations describing new political realities and cultural contexts.We are collectors of revolutionary culture: we wear it, read it, buy it, and talk about it.